A modular transformation for a generalized theta function with multiple parameters - Bhargava, S.; Mahadeva, Naika M. S.; Maheshkumar, M. C. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain a modular transformation for the theta function ∑_-∞^∞∑_-∞^∞q^a(m^2 + m^n) + cn^2 + λm + μn + ν_ςAm + Bn_ZCm + Dn, which enables us to unify and extend several modular transformations known in literature.